Healthcare leadership practice and associated factors among primary healthcare managers in East Gojam Zone, Northwest Ethiopia: a mixed method study - Endalew Minwuye Andargie; Wubshet D. Negash; Abebe Kassa Geto; Asmamaw Atnafu (BMC Health Services Research)
Abstract Background Leadership plays a critical role in the delivery of person centered, safe, efficient, and effective healthcare services globally. Poor healthcare leadership contributes to low staff motivation, patient dissatisfaction, and reduced healthcare-seeking behavior. However, there is limited evidence on healthcare leadership practice and associated factors among primary healthcare managers in the study area and at large in Ethiopia. Therefore, the findings of this study will contribute to improved healthcare leadership practices among primary healthcare managers. Method Facility-based cross-sectional study supplemented with qualitative inquiry was conducted in the East Gojam zone among 532 primary healthcare managers selected by a two-stage stratified random sampling technique. A pre-tested and structured self-administered questionnaire was used to collect the quantitative data. Data were entered into Epi-Data version 4.6 and exported into Stata version 14.0 for analysis. Multiple linear regression analysis was used to identify factors associated with healthcare leadership practice, and statistical significance was declared at a p-value < 0.05 with a 95% CI. Six key informant interviews were conducted, and thematic analysis was used for the qualitative study. Result The magnitude of healthcare leadership practice among primary healthcare managers in the East Gojam zone was 45.7% (95% CI: (41.4, 50.0)). Factors associated with healthcare leadership practice were age [β = 0.44, 95% CI: (0.16, 0.71)], training in healthcare leadership practice [β = 1.19, 95% CI: (0.19, 2.20)], experience sharing [β = 1.68, 95% CI: (0.59, 2.76)], organizational communication [β = 0.19, 95% CI: (0.05, 0.33)], managerial working experience [β = 0.94, 95% CI: (0.18, 1.69)] and emotional intelligence [β = 0.35, 95% CI: (0.31, 0.38)]. Conclusion and recommendation The magnitude of healthcare leadership practice among primary healthcare managers in the East Gojam zone was low as compared with a previous study in Ethiopia. It was significantly associated with age, training in leadership, experience sharing, organizational communication, managerial working experience, and emotional intelligence. Thus, human resource managers at primary healthcare level should consider older and more experienced candidates during assigning managers, organize training on healthcare leadership and experience sharing with model managers to improve the leadership practice of primary healthcare managers in the East Gojam zone.